Comparison of oral indices in patients with Down syndrome and healthy individuals: A meta-analysis study - Firouzeh Nilchian; Neda Mosayebi; Mohammad Javad Tarrahi; Hamidreza Pasyar (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of the present study was to compare dental indexes of pediatric Down syndrome (DS) patients to those who are healthy. Materials and Methods: This study was carried out based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement guidelines. The researchers searched title and abstract of major databases, including ProQuest (ProQuest Dissertations and Theses Full Text: Health and Medicine, ProQuest Nursing and Allie Health Source), PubMed, Google Scholar, clinical key, up to date, springer, Cochrane, Scopus, Embase, and Web of Science (ISI), up to September 2020 with restriction to English and Persian language This meta-analysis study had three outcomes: decay/miss/filled index, plaque index, and gingival index. Effect size, including mean difference and its 95% of confidence interval, was calculated. The Newcastle-Ottawa Scale measured the quality of the selected studies. Heterogeneity was performed using the Q test and I2 index, and reporting bias was assessed using a funnel plot and Egger and Begg's tests. Results: Fifteen studies conducted were included in the meta-analysis process. Conclusion: It showed that DS patients had a higher plaque index and gingival index than healthy individuals, which means that the oral health status of these patients is worse and needs more attention.